2013
DOI: 10.1088/0741-3335/55/9/093001
|View full text |Cite
|
Sign up to set email alerts
|

Sheaths in laboratory and space plasmas

Abstract: The sheaths that occur at surfaces in laboratory and space plasmas are reviewed with an emphasis on numerical models that can be solved with modest computational resources. The surfaces in plasma may be the interior walls of confinement devices or inserted probes. Fluid and kinetic models are presented in some detail, and particle-in-cell models are discussed briefly. The numerical methods find the spatial profile of the potential, the particle densities near the surfaces and the current to the surfaces. Maxwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
103
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 301 publications
2
103
0
Order By: Relevance
“…[1][2][3][4] However, many laboratory and space plasma boundaries are emissive, and the electrons emitted via process of thermionic emission, photoelectron emission and secondary electron emission (SEE) influence sheath structure dramatically, and consequently the near-wall heat flux and bulk plasma. [5][6][7][8] Therefore, understanding the characteristics of sheath near emissive surfaces is crucial for many plasma related applications and phenomena, e.g. emissive probe, 9,10 plasma thruster, 11,12 fusion reactor, 13,14 charging of spacecraft, 15,16 and dust levitation near lunar surface.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] However, many laboratory and space plasma boundaries are emissive, and the electrons emitted via process of thermionic emission, photoelectron emission and secondary electron emission (SEE) influence sheath structure dramatically, and consequently the near-wall heat flux and bulk plasma. [5][6][7][8] Therefore, understanding the characteristics of sheath near emissive surfaces is crucial for many plasma related applications and phenomena, e.g. emissive probe, 9,10 plasma thruster, 11,12 fusion reactor, 13,14 charging of spacecraft, 15,16 and dust levitation near lunar surface.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the Debye length λ D derived from the density data on Figure 4, exhibits a value of about 0.15 mm in the high density region for both field modes, similar to the radius of the CP (r p = 0.125 mm). Since traditional theories on ion collection by a cylindrical probe [3,9] require the tip radius to be much smaller than the Debye length, the CP will not be used to measure the ion density in the present experimental setup and the related mechanism for ion density correction is beyond the scope of this study.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the modeling of ion collection by a cylindrical probe (e.g., [9,19]) requires the tip radius to be much smaller than the Debye length, which is violated under the present experimental condition. Hence the CP will not be used to obtain the ion density in this study and future PIC simulations, similar to the process reported in Sheridan [12], are need to correct the ion density measured by a cylindrical probe.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations